Impact of wind power on arbitrage revenue for electricity storage. Issue 3 (1st February 2016) - Dunbar, Anna; Cradden, Lucy C.; Wallace, Robin; Harrison, Gareth P.
Abstract : Electrical energy storage provides a potential solution to the challenge of integrating large amounts of intermittent renewable energy into the electricity system. To make storage commercially viable, its operators will have to aggregate multiple revenue streams across the electricity industry. Arbitrage is recognised as one potential revenue stream. To date, wind power has provided a small contribution toward electricity generation in Great Britain (GB). Gas generators have delivered a significant proportion of total demand. Historic electricity prices reflect this, being driven principally by variations in gas price and daily demand cycles. The study reported here investigates the potential impact of wind power on electricity prices and arbitrage opportunities for energy storage in GB. Results indicate that increased wind power leads to higher price volatility for low electricity prices, but reduced frequency of higher prices which may be detrimental to storage revenue.